2019
DOI: 10.1371/journal.pone.0213220
|View full text |Cite
|
Sign up to set email alerts
|

miR-7977 inhibits the Hippo-YAP signaling pathway in bone marrow mesenchymal stromal cells

Abstract: We and others have demonstrated that various abnormalities of the bone marrow (BM) mesenchymal stromal cells (MSCs) such as aberrant cytokine expression, abnormal hedgehog signaling, and impaired miRNA biogenesis are observed in patients with acute myeloid leukemia (AML). However, underlying mechanisms to induce the dysfunction of BM MSCs have not yet been clarified. We previously showed that AML cells release abundant exosomal miR-7977, which, in turn, enters BM mesenchymal stromal cells (MSCs). However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Horiguchi H. et al found that miR-7977 was upregulated in acute myeloid leukemia and myelodysplastic syndrome and could reduce the expression of poly(rC) binding protein 1 to interfere with normal hematopoiesis. Moreover, miR-7977 was also reported to regulate the Hippo-YAP pathway, therefore inducing the upregulation of leukemia-supporting stroma growth (24,25). MiR-4286 is another miRNA that was found to be upregulated in the radioresistant group in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Horiguchi H. et al found that miR-7977 was upregulated in acute myeloid leukemia and myelodysplastic syndrome and could reduce the expression of poly(rC) binding protein 1 to interfere with normal hematopoiesis. Moreover, miR-7977 was also reported to regulate the Hippo-YAP pathway, therefore inducing the upregulation of leukemia-supporting stroma growth (24,25). MiR-4286 is another miRNA that was found to be upregulated in the radioresistant group in our study.…”
Section: Discussionsupporting
confidence: 52%
“… 46 MiR-7977 represses the Hippo-YAP signaling in BM-MSCs during AML progression. 47 In this study, we found that the expression levels of miR-425-5p were decreased in CD34+CD38āˆ’ AML cells from primary AML patients compared to that from the bone marrow of healthy cases. The expression levels of miR-425-5p were reduced in the exosomes from primary AML patients compared to those from normal cases.…”
Section: Discussionmentioning
confidence: 54%
“…Western blotting was performed as previously described (8). Briefly, separated proteins were transferred to polyvinylidene difluoride membranes and blotted with specific antibodies to detect BCL2 (at dilution of 1:500; Thermo Fisher Scientific, Inc.; #13-8800), BCLW (1:1,000; Cell Signaling Technology; cat.…”
Section: Methodsmentioning
confidence: 99%